Effect of melatonin versus vitamin D as antioxidant and Hepatoprotective agents in STZ-induced diabetic rats - Alqasim, Abdulmonim A. (J Diabetes Metab Disord, 2017)
BACKGROUND: Diabetes mellitus (DM) is a serious chronic disease, with multiple complications including hepatopathy associated with imbalance of the oxidative status. The purpose of this study is to observe possible protective effects of vitamin-D and melatonin on glucose profile, antioxidant-oxidant status, lipid peroxidation, and histopathological protection of the liver in streptozotocin-induced diabetic rats. METHODS: Eighty three male albino rats were divided into nine groups as follows: G1 (n = 10) Normal control rats; G2 (n = 8) were normal rats treated with melatonin only; G3 (n = 10) were normal rats treated with vitamin D only; G4 (n = 9) were diabetic rats, which received no medications; G5 (n = 8) were diabetic rat treated with insulin only; G6 (n = 10) were diabetic rats treated with melatonin only; G7 (n = 9) were diabetic rats treated with melatonin and insulin; G8 (n = 9) were diabetic rats treated with vitamin D only; G9 (n = 10) were diabetic rats treated with vitamin D and insulin. Two months post treatment, blood was collected to measure: Fasting blood sugar (FBS), glycosylated hemoglobin (HbA1c), fructosamine (FA), total antioxidant capacity (TAC), malondialdahyde (MDA). livers were isolated for histopathological study. RESULTS: As compared to normal rats, our results demonstrate that glucose, fructosamine and HbA1c levels is increased in diabetic groups and declined to lesser levels in treated groups. TAC level of diabetic rats is not significantly changed. Vitamin D administration significantly increased TAC while it is not changed with melatonin either in treated or non-treated groups. The liver of diabetic rats shows only mild focal microvesicular fatty degeneration. The liver of diabetic rats treated with insulin shows degeneration of cell edema in the stroma. The liver of diabetic rats treated with melatonin with or without insulin, exhibited marked improvement. The liver of diabetic rats treated with vitamin D with or without insulin, shows degeneration of cells and edema in the stroma. CONCLUSION: Our results demonstrated the beneficial antioxidant effect of vitamin D administration to normal and diabetic rats as compared to melatonin. Nevertheless, melatonin still shows more therapeutic effect on liver cell injury induced by induction of diabetes.